Risk management and risk governance of liquefied natural gas development in Gladstone, Australia. Issue 1 (January 2019) - van der Vegt, R.G.
Highlights: A retrospective analysis and post-evaluation of the implementation of risk management. The results identify a number of aspects that have influenced the risk management process. Key points to improve similar risk management problems for resource projects in the future are identified. Abstract: This paper is a retrospective analysis of the risk management and risk governance process of liquefied natural gas (LNG) development in Gladstone, Australia. In order to undertake this retrospective analysis, the risk governance framework developed by the International Risk Governance Council (IRGC) is used as a heuristic because it includes and goes beyond the ISO 31000:2009 risk approach that was used in practice. The IRGC framework consists of four different phases reflecting the risk handling chain: pre-assessment, risk appraisal, risk characterisation and evaluation, and risk management. Based on an analysis of the first three phases it was reported that the approach used by the LNG proponents in Gladstone followed relatively robust principles and guidelines despite containing a number of deficiencies. However, during the simultaneous construction of the three LNG facilities a number of environmental, social, and economic impacts and concerns emerged. Therefore, the overall aim of this paper is to explore what can be learned from this type of post-evaluation and to assess the implementation of risk management. The results identify a variety of aspects that have influenced the workability of the risk governance process and point to areas capable of improving similar problems for resource projects in the future.